Avanços e desafios nas políticas de medicamentos e assistência farmacêutica no Brasil - Thiago Botelho Azeredo (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Objective: To present the results of a pilot study of medical reconciliation performed on admission of onco-haematological patients, implemented in a public hospital in the South of Brazil. Method: This pilot study, descriptive and observational, which was conducted during January to March 2013, included patients admitted in the Hematology and Oncology Unit of Hospital Nossa Senhora da Conceição - Porto Alegre - RS. Patients and their caregivers were interviewed and their prescriptions (home and hospital) reconciled. The differences between the list of drugs that the patient is taking at home and the hospital prescriptions were categorized as intentional or unintentional discrepancies. The therapeutic drug class involved in the discrepancies was classified according to the Anatomical Therapeutic Chemical (ATC) classification. Results: From January to March 2013 were conducted 101 interviews corresponding to 89 patients. Seventeen patients were excluded from the study. The median age of patients enrolled was 55 years (14-84 years). A total of 227 medications were reconciled and identifyed 52.9% of discrepancies, with 83.3% of those, classified as intentional. An average of 1.4 discrepancies and previous use of 2.7 drugs per interview were observed. Twenty discrepancies were categorized as unintentional (17.7%). In 60% of these cases, the prescriber was reported and in 35% of cases the problem was solved, thus avoiding seven medication errors by omission of continuous use drugs. Conclusions: The results of the pilot study demonstrated that the proposed strategy was able to identify a significant percentage of discrepancies (52.9%), approaching the pharmacist of the health care team and reinforcing the importance of the implementation of this routine in the institution. Descriptors: Medication Reconciliation , Medication Errors, Patient Safety.